The sweet book of candy making : from the simple to the spectacular-how to make caramels, fudge, hard candy, fondant, toffee, and more! - LaBau, Elizabeth (Quarry Books, 2012)
"This mouthwatering book is an illustrated, comprehensive guide to candy making in three sections. Part I is a complete guide to all the ingredients and tools you need in your pantry to master the art. Part II, the bulk of the book, teaches the basics of different styles of candy, using more than 50 delicious recipes to demonstrate the techniques. You'll find chapters on all the basics, including:- Hard candies- Caramels- Toffee- Fondant- Fudge- Truffles- Fruit and nut-based candies- Marshmallows- ChocolatesPart III covers the finishing touches, including molding, piping, decorating, and presenting your candies.Sweeten up your kitchen with The Sweet Book of Candy Making!"--